Carbon Boards and Transition Risk: Explicit and Implicit exposure implications for Total Stock Returns and Dividend Payouts - Matteo Mazzarano; Gianni Guastella; Stefano Pareglio; Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 2021)
The Security and Exchange Commission (SEC) has considered climate change as a risk issue since 2010. Several emission disclosure initiatives exist aimed at informing investors about the financial risks associated with a zero or low carbon transition. Stricter regulations, particularly in a few sectors, could affect operations costs, ultimately impacting companies financial performances, especially of listed companies. There are two ways these companies can disclose their transition risk exposure and are not alternatives. One is the explicit declaration of exposure to transition risk in the legally binding documents that listed companies must provide authorities. The other is the disclosure of GHG equivalent emissions, which is implicitly associated with transition risk exposure. This paper empirically analyses to what extent US companies stock returns incorporate information about transition risk by using explicit and implicit risk measures and comparing them. In addition, multiple total stock return measures distinguishing dividend payouts from simple stock returns. Results suggest that both explicit and implicit risks are positively related to dividend payouts and not to stock returns, while the overall effect on total stock returns is negative. Evidence supports the view that market operators price negatively the transition risk exposure and, probably as a consequence, boards in carbon intensive companies use dividend policies to attract investment in risky companies.
Keywords: G35; G32; G38; Q54; 330; Climate risk; Transition Risk; SEC-10K; Mandatory Disclosure; Text analysis; CAPM